ESL Supplement (orange) : level 1. (Columbus, Ohio : SRA/McGraw-Hill, 2000)
Students who are learning to speak English as a Second Language (ESL) may need extra help with the Open Court Reading lessons. The ESL Supplement is a resource which teachers can use in providing extra help with English vocabulary and sentence structure.
Keywords: Reading--Study and teaching; Writing--Study and teaching; English language--Study and Teaching